Studies on "kansetsu-waza" (3) - Physiologie studies on "kansetzu-waza", with special reference to the reaction of the nervous and muscular systems - Ikai, M.; Asami, T.; Sasa, T. (Association for the Scientific Studies on Judo, Kodokan, 1963)
The term "Kansetsu-waza" (the art of bending and twisting the joints, bone-locks) in Judo is applied to a group of holds in which a joint of the Opponent is held and fixed at an angle other than the optimum functional angle of that particular joint, thereby making it difßcult for the muscle group which surround the joint to function efficiently, and thus enabling one to take an advantageous position over his opponent. A muscle group spanning a joint is capable of exhibiting its maximum efficiency, only when it is at its Optimum length, and when the muscle is overstretched or contracted, its efficiency is very much hindered. In view of this fact, the "Kansetsu-waza" is of great interest physiologically—it is a technique by which one is able to hold his opponent in restraint without injuring the latter, a very ingenious application of physiologic restraint. However, in the performance of the "Kansetsu-waza" this condition is advanced one step farther, and by restraining free movement of the joint of the opponent, one assumes a position which enables him to apply the decisive blow. This is done by imposing on the joint whose free movement is restrained, a load in excess to its physiologic limit, as for example in the "Juji-katame" (Cross armlock), a condition of hyperextension, and in the "Ude-garami" (Entangled armlock), a condition of hyperextension and twisting are forced on the joint. Since the scope of motion forced on the joint exceeds its physiological limit, it naturally follows that pain is feit in the joint. This is accompanied by overstretching of the ligament, and if the process is carried farther, injury to the bone may result. However, when actually performing the technique there is no intent of causing injury to the joint; the main object is to restrain free movement of the opponent, so that when the "Uke" (the individual on whom the technique is performed) feels pain in the joint he realizes that he is overcome, and the "Tori" (the performer of the technique) also realizes that his technique has taken effect, and so immediately lets go his hold. In Judo as a sport it is not desirable to go further than the point where the "Uke" feels pain. However, sometimes the whole process of the technique proceeds too rapidly for either the "Uke" or the "Tori" to realize the danger point, thereby causing undue hyperextension of the joints, or some other unphysiologic effect. For this reason it becomes necessary to clarify the effect upon the human body when these conditions are imposed on the joints. The present study was undertaken with the view of investigating particularly the effect on the nervous and muscular systems,